Role of serum copper and lipid profile in cardiovascular diseases patients of Southern Rajasthan - Dhanak, Parul; Sharma, Neha; Sharma, Ashish (International Journal of Research in Medical Sciences, 2019)
Background: It is clear that deficiencies of some trace elements cause marked alterations in lipid and lipoprotein metabolism. The mechanisms of their effects are not completely obvious and inspite of intense research, the role of these microelements need further elucidation. Thus, the objective of this study is to evaluate the correlations of serum concentrations of trace elements including copper with lipid profile parameters of adult men in Southern Rajasthan. Methods: Present study was conducted in Cardiology and Biochemistry Department in GMCH, Udaipur during the year 2019. A total of 150 MI cases/controls were selected. Blood sample was collected by vein puncture using an aseptic technique. The blood was allowed to settle at 37ºC and then centrifuged at 3000 rpm for 15 min. Serum was then separated and stored at -20ºC until analysis. Results: The study cases had significantly higher lipid values than those of controls (p<0.001). In cases the copper levels are higher than the controls. Copper levels were more in males 95.40±18.93 than in females 86.93±14.54 (p<0.05). Lipid levels were higher in urban population related to rural, TC (238.47 V/s 266.59), TG (219.83 V/s 202.40), HDL (64.39 V/s 54.19) and LDL (131.28 V/s 139.48) (p<0.05). Significant negative correlation was seen in study group between serum copper levels and TC (r=-0.288, p<0.05), TG (r =-0.236, p<0.05), HDL (r=-0.946, p<0.05) and VLDL levels (r=0.102, p<0.05). This indicates that as copper level reduces lipids increases. Conclusions:Our findings indicate the possible effect of Cu level in serum lipid profile and this effect may be due to the role of Cu as an antioxidant. The correlations between the serum concentrations of trace elements with lipid profile in physiological concentrations may not be the same as the changes observed during deficiencies of the trace elements as in hyperlipidemic patients